The Link Course Programme Proposals for Policy Development. Discussion Paper - Brunner, S.; Daley, M.; National TAFE Clearinghouse, Adelaide (Australia). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Existing Department of Technical and Further Education (TAFE) policy and practice in link courses are reviewed, and some proposals are made on the development of that policy. Issues or questions raised by these policies are juxtaposed with the presentation of link program policy. Chapter 1 considers the background of the link course program and defines the link program as being comprised of part-time courses usually conducted within a TAFE institution to offer secondary students a sample of a wide range of employment areas. Bases of operation for the link program are discussed in chapter 2. These include mutual commitment and mutual planning by secondary schools and TAFE institutions, use of exclusive resources, access to an adult learning environment, curriculum guidelines, cautions related to narrowing students' vocational options in link courses, counseling, and staff development. Chapter 3 focuses on data collection policy. The 1982 record-keeping situation is summarized; an assessment of commitment/cost is outlined, and a centralized transitional education record system is proposed. Chapter 4 addresses the priorities and responsibilities for financing. Appendixes include an interim link course policy and record-keeping forms. (YLB)
Policymakers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Articulation (Education); Coordination; Curriculum; Educational Cooperation; Educational Planning; Educational Policy; Foreign Countries; Policy Formation; Postsecondary Education; Program Development; Secondary Education; Vocational Education; Australia (South Australia) -- Linked Courses; Opinion Papers